Ketahanan kedelai varietas Detam 3 hasil iradiasi sinar gamma di tanah salin - Awang Ghosypea; Sutarno Sutarno; Florentina Kusmiyati (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
Mutation is one of a breeding technique to modify plant’s genetic. The purpose of study was to evalauate effect of gamma irradiation on M1 soybean variety Detam 3 based on agronomic characteristic at saline soil (2 dS/m). Gamma iradiation applied were 160, 208, 256, 304, 352, 400, 448, 496, 544, 592, 640 Gy. Parameters observed were plant height, number of leaves, number of pods, weight of pods, number of seeds, and seed weight per plant. The results showed that 10 plants classified as moderate, 4 plants classified as tolerant, and 2 plants classified as most tolerant at saline soil (2 dS/m).Keywords: Detam 3, gamma, irradiation, saline soil, soybean.